O boom do dendê na microrregião de Tomé-Açu, na Amazônia paraense - João Santos Nahum; Cleison Bastos dos Santos (Confins)
In this paper we analyze the expansion of oil palm cultivation in the micro-region of Tomé-Açu, in the Brazilian Amazon state of Pará. What landscape changes, in the spatial configuration, social dynamics, and utilized territory can we identify in this commodity boom? We begin by analyzing lands under oil palm cultivation, which lets us consider oil palm as a specific event and affirm that we are on the cusp of a oil palm boom being undertaken by territorial networks of oil palm producers. We base this analysis in interviews, data collection, maps, and field work since 2008 in the municipalities of Moju, Acará, Tailândia, Tomé-Açu, and Concórdia do Pará, where African oil palm monocultures are expanding. This requires a geographic examination, attentive to the uses and abuses of the territory.